A genome-wide association study on a southern European population identifies a new Crohn's disease susceptibility locus at RBX1-EP300. Issue 10 (30th August 2012) - Julià, Antonio; Domènech, Eugeni; Ricart, Elena; Tortosa, Raül; García-Sánchez, Valle; Gisbert, Javier P; Nos Mateu, Pilar; Gutiérrez, Ana; Gomollón, Fernando; Mendoza, Juan Luís; Garcia-Planella, Esther; Barreiro-de Acosta, Manuel; et al.
Abstract : Objective: Genome-wide association studies (GWAS) have identified multiple risk loci for Crohn's disease (CD). However, the cumulative risk exerted by these loci is low, and the likelihood that additional, as-yet undiscovered loci contribute to the risk of CD is very high. We performed a GWAS on a southern European population to identify new CD risk loci. Design: We genotyped 620 901 genome markers on 1341 CD patients and 1518 controls from Spain. The top association signals representing new candidate risk loci were subsequently analysed in an independent replication cohort of 1365 CD patients and 1396 controls. Results: We identified a genome-wide significant association on chromosome 22q13.2 in the intergenic region between the RBX1 and EP300 genes (single nucleotide polymorphism rs4820425, OR 1.27, 95% CI 1.17 to 1.38, p=3.42E-8). We also found suggestive evidence for the association of the IFNGR2 (21q22.11), FOXP2 (7q31), MACROD2 (20p12.1) and AIF1 (6p21.3) loci with CD risk. Conclusions: In this GWAS performed on a southern European cohort, we have identified a new risk locus for CD between RBX1 and EP300 . This study demonstrates that using populations of different ancestry is a useful strategy to identify new risk loci for CD.